Post-War Reconstruction of Ukraine – Parallels of the Post-War Reconstruction of Germany - Müller, W.; Khrystoforova, O. M.; Lyashenko, V. (IJAMSR, 2022)
Post-war reconstruction is one of the key elements of the rebirth of a new life in economic, social, political and cultural aspects. At the same time, the main role in such processes is given to economic recovery. In this aspect, it is taxation that can be the driving force behind economic revival. The paper examines the parallels of economic recovery in post-war Germany, outlines the basic principles for building an equitable and effective taxation system.
Keywords: post-war reconstruction; principles